Development of Social Competence through Play Activities: Lost in the Digital Age - Dasmadi; Mathew Alfredo Joseph Kaunang; Endang Fatmawati; Sahrul Ari Irawan; Enrile Victorio (ENDLESS: INTERNATIONAL JOURNAL OF FUTURE STUDIES, 2023)
Technological developments in the digital era have generally changed children’s play activities. Even though there are many digital games nowadays, the social interactions that usually occur in traditional games are slowly disappearing. This research will then be carried out to see the development of children’s loss of social competence when playing. This research will be carried out using a qualitative approach. Through literature studies, researchers use secondary data derived from various research results and previous studies which still have relevance to the content of this research. The results of this study then found that traditional games can increase a child’s interaction to improve social competence in the child. However, the emergence of technology in the digital era is slowly eroding traditional games. The consequence is reduced social interaction that occurs in children so that later the development of their social competence also disappears in this digital era.